Education and science: current trends - Krapostin A. A., Vereshchaka A. S., Sotova E. S., Vereshchaka A. A., Krasnovskii A. N., Chuyan E. N., Ravaeva M. Y., Baranov G. V., Yusupova L. G., Kireeva N. A., Redko A. M., Shutenko E. N., Alekseeva E. S., Demidenko L. L., Saltykova M. V., Starygina S. D., Nuriev N. K., Zhdanova S. N., Bespalova V. V., Polianskaia O. A., Kadyrova O. V., Domanska L., Chmyreva M. I., Drozhzhina N. B. (Education and science: current trends, 2016)
the labour market is a place where a constant competition between candidates eager to get employment and those who want to maintain it takes place. Of course, the best chance of getting a job have people who are educated and qualified in occupations within a deficit group. We cannot forget that nowadays on the labour market there is a surplus of labour supply over demand. With such a competition, little chance of getting a job have people affected by social exclusion. They are, among others, people with disabilities, including intellectual ones. Another problem is the demographic changes observed in many countries of the world, which indicate that due to low population growth and lack of direct replacement of generations, the labour market will run out of hands to work. As a result of this, in many countries working age is extended. Authors assume that such treatments may not be sufficient and countries will have to use the resources previously unaccounted for or included in a small proportion, for example people with disabilities. This paper introduces reader to the system of supported employment. This concept, although new, is gaining more and more supporters. In the study the authors focus special attention on the future profession – job coach. They describe the qualifications necessary to perform this function, and also show the forms of professional development of a person employed for the job.
Keywords: профессиональное развитие; квалификационные требования; professional development; инструктор по поиску рабочего места; работник с ограничениями к трудовой деятельности; поддерживаемая занятость; job coach; qualifications; disabled employee; supported employment